Optimalisasi Aksesibilitas Sebagai Percepatan Pembangunan : Studi Kasus Penataan Jalan di Kabupaten Pangandaran - Kharisma, Bayu; Triwardani, Wulan Agustina (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.07.NO.05.TAHUN 2018DO - 10.24843/EEB.2018.v07.i05.p07, 2018)
This study aims to analyze the implementation of infrastructure development, especially the arrangement of roads, road management policy in terms of spatial aspects and accessibility of development in Pangandaran Regency. The methodology used in this research is Connectivity, Ultrasound Method and SWOT Analysis. Source of data used as informants is Bappeda Pangadaran District and Local Government Work Unit (SKPD) and RPJMD document Pangandaran District 2016-2021, Regional Profile of Regency Pangandaran 2106. The official map of Pangandaran Regency to be used as reference to analyze spatially. In addition, the process of collecting data using interview methods accompanied the demand for digital data. The results showed that the implementation of infrastructure development related to road arrangement in Pangandaran Regency is currently the main priority of development activities. It is not separated that the existing road conditions can be said to be less feasible and is a legacy of Ciamis regency. The policy of road arrangement is urgent because if viewed from the spatial aspect of Pangandaran Regency is in disaster-prone areas. On the other hand, the challenging condition of topology and geography of Pangandaran Regency becomes its own reasons. Accessibility can increase the acceleration of development in Pangandaran regency due to the strategic location of Pangandaran Regency and become a tourist destination